2013
DOI: 10.1002/wrcr.20210
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous turbulent forces and impulse on a rough bed: Implications for initiation of bed material movement

Abstract: [1] The overall objective of this study is to identify the physical mechanisms responsible for the entrainment of an exposed particle subject to rapidly fluctuating hydrodynamic forces in the case of channel flow with a fully rough boundary. This is pursued here by examining particle dislodgment under uniform and cylinder wake-flow experiments. The critical impulse concept is investigated more rigorously by measuring directly the pressures at four points on the surface of a fixed test grain. The number of impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 25 publications
6
43
0
Order By: Relevance
“…As shown in the marked section, negative lift forces (downward) induce the extra resistance by increasing the counter moment to prevent particle motion. A similar observation was reported by Celik et al (2013). Note that the moment of lift forces is incorporated in the torque computation (equation (3)).…”
Section: Dynamic Particle Resistancesupporting
confidence: 80%
See 3 more Smart Citations
“…As shown in the marked section, negative lift forces (downward) induce the extra resistance by increasing the counter moment to prevent particle motion. A similar observation was reported by Celik et al (2013). Note that the moment of lift forces is incorporated in the torque computation (equation (3)).…”
Section: Dynamic Particle Resistancesupporting
confidence: 80%
“…To determine the hydrodynamic forces applied on a sediment particle, the results from a laboratory study reported in Celik et al (2013) are employed in this paper. In their experiments, four synchronized pressure transducers are mounted on a target sphere of 12.7 mm in diameter, which is fixed within a pocket formed by three hexagonal, well-packed identical spheres ( Fig.…”
Section: Experiments and Equations Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that sweeps and inward interactions are correlated with the initial entrainment of sediment (Fig. 7) and/or produce larger bedload fluxes than other events (bursts, inward interactions) of the same magnitude (e.g., Nelson et al, 1995;Dwivedi et al, 2011;Wu and Shih, 2012;Celik et al, 2013). It has been hypothesized that because bursts and outward interactions are associated with positive streamwise velocity fluctuations, the instantaneous streamwise velocity rather than the vertical velocity dictates particle motion.…”
Section: Grain Scale Transport Mechanicsmentioning
confidence: 99%